2021
DOI: 10.2147/ijn.s299681
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Self-Assembled Drug Delivery for Effective Anti-Breast Cancer Therapy

Abstract: The metastasis of breast cancer is an important cause of tumor recurrence. This study highlights that tyrosine kinase inhibitors dasatinib (DAS) and rosiglitazone (ROZ) inhibit tumor growth and reduce the occurrence of tumor cell metastasis. Due to the poor water solubility, short half-time in the body of DAS and ROZ, which increases the difficulty of tumor treatment, as well as the demand for nano-drug delivery systems for organ-specific therapies. Methods: Hyaluronic acid (HA) and DAS are bonded by a pH-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Rosiglitazone maleate has traditionally been widely used to reduce sugar in the blood of patients with diabetes mellitus (Zhao et al, 2021). However, investigators have recently demonstrated that rosiglitazone maleate also has a therapeutic effect on various cancers, including lung cancer, breast cancer, and pancreatic cancer (Dang et al, 2018;Wang et al, 2020;Wu et al, 2020;Wang et al, 2021;Zhou et al, 2021). We found that rosiglitazone maleate had a significant therapeutic effect on RD cells and inhibited RD cell proliferation by mediating the PPARG pathway.…”
Section: Discussionmentioning
confidence: 68%
“…Rosiglitazone maleate has traditionally been widely used to reduce sugar in the blood of patients with diabetes mellitus (Zhao et al, 2021). However, investigators have recently demonstrated that rosiglitazone maleate also has a therapeutic effect on various cancers, including lung cancer, breast cancer, and pancreatic cancer (Dang et al, 2018;Wang et al, 2020;Wu et al, 2020;Wang et al, 2021;Zhou et al, 2021). We found that rosiglitazone maleate had a significant therapeutic effect on RD cells and inhibited RD cell proliferation by mediating the PPARG pathway.…”
Section: Discussionmentioning
confidence: 68%
“…HA-DAS polymer was synthesized by our research group and the structure was confirmed by 1 H-NMR. 37 In short, EDCI and DMAP were used to activate the carboxyl group of HA in deionized water, and then DAS was added to form the HA-DAS polymer by ester bond.…”
Section: Methodsmentioning
confidence: 99%
“…HDO-NPs were hydrolyzed by strong alkaline hydrolysis to determine the drug loading and encapsulation efficiency of DAS and OLA. 37 , 38 In short, 4 mg HDO-NPs were dissolved in 1 mL deionized water, 100 μL NaOH (1 mol/L) was added for 0.5 h, and then 100 μL HCl (1 mol/L) was added for neutralization. Subsequently, 3 mL methanol was added to dissolve the cracked DAS and OLA, which were mixed evenly and centrifuged (5000 rpm, 10 min).…”
Section: Methodsmentioning
confidence: 99%
“…The developed THDR-NPs showed better efficacy than the taking of free TKIs. In addition, the capacity of THDR-NPs to prevent tumor metastasis has been demonstrated (58). Another study using micelle nanoparticles to deliver anlotinib also showed a more effective uptake to the melanoma cells (59).…”
Section: Nanotechnology As the Potential Delivery Systemmentioning
confidence: 97%